Evaluation of Tumour Budding in Head and Neck Squamous Cell Carcinoma and Its Relationship with other Histological Parameters of Prognosis - Ghosh, Shreshtha; Guha, Priyadarshini (Asian Pacific Journal of Cancer Biology, 2023)
Background: Tumor budding (TB) is an emerging and promising histopathological prognostic parameter in oral squamous cell carcinoma (SCC). Tumour budding shows positive correlation with lymph node metastasis, higher pattern of invasion, high grade of tumor and more depth of invasion. These histopathological parameters are associated with poor prognosis, high rate of recurrence and these prognostic factors can be routinely used by clinicians for planning of multimodality treatment. Method: The present study was a cross-sectional study carried out on total of 239 patients with oral squamous cell carcinoma who attended the surgical oncology unit of Kalyan Singh Super Speciality Cancer Institute, Lucknow, Uttar Pradesh, India, from November 2020 to June 2022. Descriptive statistical analysis has been carried out in the present study. We used Fischer Exact Probability test and chi-square test analysis in order to identify relationship between different histological features, significance was considered when p<0.05. Results: Majority of study population (69.87%) were in the age group of less than 54 years of age. Age group (<54years) was significantly associated with tumor budding (p<0.05). Cases diagnosed as moderately differentiated SCC were 68.6 % and well differentiated SCC were 25.1%. 74 cases were associated with high intensity of tumor budding and 59 cases with low intensity of tumor budding (p<0.05). Most common worst pattern of invasion was type 4 (61.9%) followed by type 5 (26.4%), strong statistical association was observed with intensity of tumor budding (p<0.05). Most of the cases exhibited maximum depth of invasion (DOI) >1cm (100 cases). DOI was significantly associated with intensity of tumor budding (p<0.05). Out of 102 involved lymph node cases, 91 cases were associated with tumor budding 55 cases of these associated with high intensity tumor budding. Tumor budding was also significantly associated with lymph node metastasis (p<0.05). Conclusion: Present study showed a strong correlation of tumor budding with lymph node metastasis, depth of invasion and worst pattern of invasion. Thus, this study emphasizes the importance of tumor budding evaluation in routine pathology reporting and similar to depth of invasion TB should be included in AJCC TNM staging.